2019
DOI: 10.1155/2019/5418041
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impacts of Climate Change on Climatic Zones over the Korean Peninsula

Abstract: In assessing the impact of climate change, the use of a multimodel ensemble (MME) is required to quantify uncertainties between scenarios and produce downscaled outlines for the simulation of climate under the influence of different factors including topography. This study of climate change scenarios from 13 global climate models (GCMs) assesses the impacts of future climate change. Unlike South Korea, North Korea lacks studies using climate change scenarios of the Coupled Model Intercomparison Project Phase 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Our findings showed that a higher prevalence of T. orientalis was recorded in regions that were closer to the equator. Since it is predicted that the southern regions of Korea are subject to warmer temperatures and higher weather variations than the northern regions [ 19 ], the tick distribution could be more prevalent because of the more favorable warm habitat [ 26 ]. This finding is similar to that of a study conducted in New Zealand from 2012 to 2013, where the prevalence of bovine anemia due to Theileria -associated anemia was significantly higher in cattle herds on North Island, which experiences subtropical weather during the summer, than in those on South Island [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that a higher prevalence of T. orientalis was recorded in regions that were closer to the equator. Since it is predicted that the southern regions of Korea are subject to warmer temperatures and higher weather variations than the northern regions [ 19 ], the tick distribution could be more prevalent because of the more favorable warm habitat [ 26 ]. This finding is similar to that of a study conducted in New Zealand from 2012 to 2013, where the prevalence of bovine anemia due to Theileria -associated anemia was significantly higher in cattle herds on North Island, which experiences subtropical weather during the summer, than in those on South Island [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, according to Köppen-Geiger climate classification, South Korea mainly has a monsoon-influenced hot-summer humid continental climate (Dwa), hot-summer humid continental climate (Dfa), and humid subtropical climate (Cfa). Seoul has a Dwa climate [43,44]. Utilizing Diva for Rhino-Grasshopper [45], which can extract solar vectors over time, an algorithm was developed to identify the sunshine hours of each of the residential units and whether the units met the requirement of more than two consecutive sunshine hours.…”
Section: Methodsmentioning
confidence: 99%
“…Köppen-Geiger climate classification of South Korea: Monsoon-influenced hot-summer humid continental climate (Dwa), hot-summer humid continental climate (Dfa), and humid subtropical climate (Cfa). Seoul has a Monsoon-influenced hot-summer humid continental climate (Dwa) [43,44].…”
mentioning
confidence: 99%
“…The GCMs selected in this study have been evaluated to have excellent performances East Asia (GISS‐E2‐R and INM‐CM4: Preethi et al ., 2017; ACCESS1.3: Bell et al ., 2019). The intention was to explore the changes in the projections of these frequently used CMIP5 GCMs for SSP scenarios (Eum and Cannon, 2017; Jeung et al ., 2019; Prasanna et al ., 2020; Song et al ., 2020). The SSP scenario of CMIP6 includes social and economic factors with the emission scenarios of RCP (O'Neill et al ., 2017).…”
Section: Study Area and Datamentioning
confidence: 99%